PENGARUH METODE GLOBAL BERBANTUAN MEDIA FLASHCARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS I SEKOLAH DASAR - Noni Ragelia; Satrio Wibowo; Galuh Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study started with the issue of the first-grade kids at Sugihwaras Elementary School having low beginning reading abilities. To determine the level of influence produced, a global-assisted approach with flashcard media is used in Indonesian language subjects. The experimental quantitative methodology and Nonequivalent Control Group Design were employed as the research method. Class IA 30 experimental students and class IB 30 control students were chosen using the Purposive Sampling Technique. The instrument consists of an oral test sheet in the form of a pretest-posttest for beginning reading and a student activity sheet. The posttest average score of 73.6 exceeds the pretest score of 54.6, showing that the experimental group has improved. The pretest score for the control group was 52.1, while the posttest score was 56.8. The Sig. (2-tailed) 0.000 <0.05 is demonstrated by the t-test findings. An average of 84% of the students in the experimental class were engaged in positive activities. The findings show that the global method, aided by flashcard media, influences the beginning reading skills of grade I pupils at Sugihwaras Elementary School.